Efektivitas Pemberian Makanan Tambahan Dengan Konsep Empat Bintang Terhadap Kenaikan Berat Badan Balita Gizi Buruk Di Posyandu Wilayah Puskesmas Ngawen Kabupaten Klaten - Anik Kurniawati; Endang Suwanti (Interest : Jurnal Ilmu Kesehatan, 2017)
Abstract: Toddler, PMBA, Malnutrition. Background, Klaten district shows the incidence of malnutrition as many as 479 infants and less than 2,890 children under five nutrition, one in Ngawen health ceter in Candirejo village has 3 malnourished children under five and 21 toddler less nutrition, the participation rate of toddler to posyandu also still below target that is 80, 35 %% while the weight gain rate of children under 5 years old is still under the target of 72,75%, and Mayungan Village there are 7 children under five with malnutrition status and 37 under fives with less nutritional status. While the rate of weight gain that comes to be weighed to posyandu is still under the target of 58.54%. Some mothers said that children underweight and malnutrition caused by toddlers difficult to eat. Some of the problems that many occur at the beginning of infant feeding is the lack of food variations given by parents, especially fruit, vegetables and animal side dishes. The purpose, to determine the effectiveness of additional food description with the concept of four stars to increase weight toddler malnutrition in Posyandu area Ngawen Puskesmas Klaten District. The research hypothesis, supplementary food queue with the concept of four stars effectively increase the weight of malnutrition toddler at Posyandu of Puskesmas Ngawen Region, Klaten Regency. Research Method, This research type is experiment, with approach of quasi ekapeiment with design of Nonequivalent Control Group Design. Target population in this research is all toddler malnutrition in posyandu of puskesmas ngawen area counted 24 toddler. Sampling technique in this study is purposive sampling, toddlers taken into the sample is a toddler who is not getting another treatment for 18 toddler. Data analysis using independent t test test hypothesis test using Anava Friedman test. The results showed normal distributed data. Independent test of t-Test shows sig value (0.000) <0,05. This means that there are significant differences in body weight of pre-test and body weight of post test with correlation of 0.995. Hypothesis test results show data that sig value (0.008) <0.05 supplementary feeding with the concept of 4 stars effectively increase the weight of children under five with malnutrition in posyandu of puskesmas Ngawen subdistrict Ngawen Sub-district of Klaten Regency.